2009
DOI: 10.1111/j.1468-1331.2009.02653.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100B protein in early management of patients after mild traumatic brain injury

Abstract: S100B serum protein marker seems to be an unrealiable screening tool for determination of an intracranial injury risk group due to low sensitivity and negative predictive value seen from samples taken greater than 3 h after an MTBI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 34 publications
(48 reference statements)
2
24
0
3
Order By: Relevance
“…In all of these series, serum levels of S100B failed to efficiently identify children with intracranial pathology on imaging studies. 1,3,8 These findings agree with those in the mild TBI study by Morochovic et al, 16 which showed that S100B is an unreliable screening tool for detecting intracranial pathology in adults and children. On the other hand, the study by Castellani et al 4 identified a role for S100B in the initial evaluation of children with mild TBI.…”
supporting
confidence: 82%
See 1 more Smart Citation
“…In all of these series, serum levels of S100B failed to efficiently identify children with intracranial pathology on imaging studies. 1,3,8 These findings agree with those in the mild TBI study by Morochovic et al, 16 which showed that S100B is an unreliable screening tool for detecting intracranial pathology in adults and children. On the other hand, the study by Castellani et al 4 identified a role for S100B in the initial evaluation of children with mild TBI.…”
supporting
confidence: 82%
“…The sampling time of S100B in relation to the time of head injury is also an important factor that may influence its serum concentrations and thus make the interpretation of any S100B increases inconclusive in TBI cases. 8,16 Delayed serum measurements of S100B following a head injury may lead to erroneous conclusions regarding the severity and extent of neuronal damage, because of the relatively short half-life of the S100B protein. Geyer et al 8 emphasized the importance of the time span between injury and S100B blood sampling in the accurate measurement of S100B serum levels.…”
Section: Discussionmentioning
confidence: 99%
“…The design and patient characteristics of the 12 studies 98,113,115,130,[143][144][145][146][147][148][149][150] that evaluated the diagnostic accuracy of various biochemical markers for diagnosing ICI (including the need for neurosurgery) in adults and children with MHI are summarised in Table 18. Nine studies provided diagnostic data on protein S100B only, 98,113,115,[143][144][145][146][147][148][149] one on NSE only 115,130 and one on other markers [creatine kinase isozyme (CK-BB), noradrenaline, adrenaline, dopamine, amylase and total catecholamines].…”
Section: Description Of Included Studies (Design and Patient Charactementioning
confidence: 99%
“…Previous studies identified maximum sensitivity for abnormal head CT at an S100B level of 0.10-0.12 lg/L. 9,10,[25][26][27][28][29] In our cohort, the 98% sensitivity level was not reached until the S100B level was below 0.060 lg/L. At a cutoff of 0.10 lg/L, the FIG.…”
Section: Discussionmentioning
confidence: 66%